PENDETEKSIAN SOURCE CODE PLAGIARISM DENGAN ALGORITMA RABIN-KARP PADA ONLINE JUDGE - YUNUS FADHILLAH (Jupiter: Journal of Computer & Information Technology, 2021)
The difficulty of testing the truth of the source code and the detection of plagiarismsource code is the underlying problem of this research. The string matchingalgorithm is the main algorithm required in the detection of source code plagiarism.Currently, there are many existing strings matching algorithms, therefore it isnecessary to compare and select the appropriate string matching algorithm to theexisting requirement. As for the system, the researcher conducts a literature study and direct observation to find the appropriate source code testing system. The Rabin-Karp algorithm is chosen based on the average of a good time and space complexity. And also can be modified, so that the Rabin-Karp algorithm can be made in such a way that can meet all the needs that exist. As for the system testing source code researchers choose the online judge system because the system in the test is objective.